Web-based computer application for tick identification in Tunisia - CGIAR Research Program on Livestock (2021)
Out of the five tested models, “YOLOv5” achieved the best detection performance with a precision (AP) of 0.76. An experimental information architecture (IA) prototype is available for tick identification. Ongoing work aims at improving its performance under controlled conditions and assessing its reliability under field conditions.